Olanzapine-Induced Hyperprolactinemia: Two Case Reports - Pedro Cabral Barata; Mário João Santos; João Carlos Melo; Teresa Maia (Frontiers Media S.A., 2019)
Background: Hyperprolactinemia is a common consequence of treatment with antipsychotics. It is usually defined by a sustained prolactin level above the laboratory upper level of normal in conditions other than that where physiologic hyperprolactinemia is expected. Normal prolactin levels vary significantly among different laboratories and studies. Several studies indicate that olanzapine does not significantly affect serum prolactin levels in the long term, although this statement has been challenged.Aims: Our aim is to report two olanzapine-induced hyperprolactinemia cases observed in psychiatric consultations.Methods: Medical records of the patients who developed this clinical situation observed in psychiatric consultations in the Psychiatry Department of the Prof. Dr. Fernando Fonseca Hospital during the year of 2017 were analyzed, complemented with a non-systematic review of the literature.Results: The case reports consider two women who developed prolactin-related symptoms after the initiation of olanzapine. No baseline prolactinemia was obtained, and prolactin serum levels were only evaluated after prolactin-related symptoms developed: at the time of its measurement, both patients had been taking olanzapine for more than 24 weeks. Hyperprolactinemia was found to be present in Case 2, whereas Case 1 (a 49-year-old woman) had "normal" serum prolactin levels for premenopausal and prolactin levels slightly above the maximum levels for postmenopausal women. Both patients underwent similar pharmacological adjustments, which comprised switches from olanzapine to aripiprazole. After all pharmacological changes, prolactin serum levels decreased to normal range values and prolactin-related symptoms disappeared.Discussion/Conclusions: Laboratorial and literature prolactinemia values variability and discrepancies may make the management of borderline hyperprolactinemia clinical situations difficult. Baseline prolactin levels should have been obtained, as they help in the management of patients who develop neuroleptic-induced hyperprolactinemia. Prolactin-related symptoms can occur with borderline or normal standardized prolactinemia values. Olanzapine-induced hyperprolactinemia is a rare but possible event. Aripiprazole was used as a suitable alternative for olanzapine-induced hyperprolactinemia.